Transient dynamics of a full wheel rail set passing a weld irregularity at high speed. (June 2023) - Liu, X.; Liu, C.; Wu, W.; Liu, J.Z.; Sun, S.C.; Wei, Y.G.
Highlights: We developed a transient model for studying a full wheel set passing weld irregularities. We proposed a standard safety limit for the driving speed. Presented model can consider both the concave and convex weld. Abstract: Compared to tracking the contact force, the monitoring of axle box acceleration ( ABA ) is an effective way to determine the operation status of a high–speed train passing a weld. In this study, we propose a finite element model for studying the dynamic response of a full wheelset passing weld irregularities at high speed. Simulations provide detailed dynamic information during the pass, such as the peak of the contact force and the history of acceleration. With these simulation results, we propose a standard safety limit for the running speed: a running speed boundary as a function of defect size. Additionally, rail weld defect grinding standards should depend on the running speeds.